Fairclough's Critical Discourse Analysis on News Texts on "Merdeka Belajar Kampus Merdeka (MBKM)" in Kompas.com - Prawoto, Eko Cahyo (Bahasa: Jurnal Keilmuan Pendidikan Bahasa dan Sastra Indonesia, 2022)
Improving the quality of education is so important, the government through the Ministry of Education, Culture, Research and Technology takes strategic steps, one of which is the implementation of MBKM. The MBKM program is socialized through the Ministry of Education and Culture's Website and through mass media. The mass media has always been active in assisting the government in socializing the program to the public. Therefore, a critical discourse study is needed to determine the relationship between the discourse in the news text about the program and the current state of education. Critical Discourse Analysis put forward by Norman Faircglough is used as a theoretical basis in this study. The research method used is a descriptive qualitative method. The source of the data in this study is a news article in the Kompas.com about MBKM, then the data in this study is a discourse that contains microstructural, mesostructural, and macrostructural dimensions that can be related to the phenomenon or condition of education in Indonesia at this time. Furthermore, the data collection of this study was carried out through several stages; a) identification, b) encoding, c) writing data. Then on data analysis is carried out through; a) classification of data, b) presentation of data, c) interpretation of data, d) retrieval of conclusions. The results obtained in this study are there; a) textual dimension (microstructural) b) dimension of discourse (mesostructural), and c) macrostructural social dimension.AbstrakPeningkatan kualitas pendidikan begitu penting, membuat pemerintah melalui Kementrian Pendidikan, Kebudayaan, Riset dan Teknologi mengambil langkah-langkah strategis, salah satunya ialah implementasi MBKM. Program MBKM disosialisasikan melalui Website Kemendikbud Ristek serta melalui media massa. Media massa selalu aktif membantu pemerintah dalam menyosialisasikan program tersebut kepada masyarakat. Oleh sebab itu, diperlukan kajian wacana kritis untuk mengetahui hubungan antara wacana dalam teks berita tentang program tersebut dengan kondisi pendidikan saat ini. Analisis Wacana Kritis yang dikemukakan oleh Norman Fairclough digunakan sebagai pijakan teori pada penelitian ini. Metode penelitian yang digunakan ialah metode kualitatif deskriptif. Adapun sumber data pada penelitian ini ialah artikel berita di Kompas.com tentang MBKM, selanjutnya data pada penelitian ini ialah wacana yang mengandung dimensi mikrostruktural, mesostruktural, dan makrostruktural yang dapat dikaitkan dengan fenomena atau kondisi pendidikan di Indonesia pada saat ini. Selanjutnya, pengumpulan data penelitian ini dilakukan melalui beberapa tahapan; a) pengidentifikasian, b) pengodean, c) penulisan data. Kemudian pada analisis data dilakukan melalui; a) pengklasifikasian data, b) penyajian data, c) penginterpretasian data, d) pengambilan simpulan. Adapun hasil yang diperoleh pada penelitian ini ialah terdapat; a) dimensi tekstual (mikrostruktural), b) dimensi kewacanaan (mesostruktural), dan c) dimensi sosial makrostruktural.